The Tribological Properties of Cutting Tools and Suitable Conditions for Turning Alloy Steel for Producing Excavator Parts - Khunead, Chalerm; Watcharasresomroeng, Bhadpiroon (RMUTL Engineering Journal, 2020)
The objective of this study is to investigate the tribological properties of cutting tools and the suitable conditions for turning alloy steel for the manufacturing of excavator parts. The cutting tool studied is made of cemented carbide material coated with hard thin films of TiCN+Al2O3 and TiCN by CVD and PVD processes. The mechanical properties of the cutting tools with a thin film coating are investigated by nanoindenter techniques. The tribological properties between the contacting surfaces of the cutting tool material and the workpiece material are evaluated with simulation testing by Pin-on-Disk in accordance with ASTM G99-95a. In order to be effective in terms of production time, turning of the workpiece material is set to a constant cutting speed of 175 m/min during the experiment, which is the fastest value according to the manufacturer’s recommendation. The studied factors in the turning process include feed rates and cutting depths. From the study, it was found that the cutting tool coated with TiCN+Al2O3 film by CVD process, which had the highest hardness in this study, gave the lowest coefficient of friction between the contacting surfaces as 0.343. It is a suitable cutting tool for turning alloy steel for producing excavator parts. The workpieces had the lowest Ra surface roughness when using a feed rate and a cutting depth of 0.10 mm/rev and 0.50 mm, respectively.